Non-medical treatment for late age-related macular degeneration - A.K. Drakon; A.G. Kurguzova; V.M. Sheludchenko; N.B. Korchazhkina (РМЖ "Клиническая офтальмология")
A.K. Drakon1, A.G. Kurguzova1, V.M. Sheludchenko1, N.B. Korchazhkina2 1Scientific Research Institute of Eye Diseases, Moscow, Russian Federation 2Academician B.V. Petrovskiy Russian Scientific Center of Surgery, Moscow, Russian Federation   Age-related macular degeneration (AMD) is the leading cause of blindness in people over 55 in developed countries. Moreover, the number of these patients will increase growth as life expectancy increases. It is estimated that late AMD accounts for half of blindness and low vision cases in European countries. A myriad of studies is currently underway to discover cutting-edge, effective therapeutic modalities. Gene therapy is a novel alternative to regular intravitreal injections of anti-VEGF agents for late wet AMD. This technique’s heart is a specific gene delivery to target cells to generate natural VEGF inhibitors. Gene therapy affecting the complement system to deactivate its end product, the membrane attack complex, is reasonable in late atrophic AMD. Studies on stem cell therapy for late atrophic AMD undergo as well. It was demonstrated that retinal pigment epithelium (RPE) cells derived from human embryonic stem cells or induced pluripotent stem cells express typi cal RPE markers that can phagocytize photoreceptor segments. Electrical stimulation and magnet therapy are already introduced into clinical practice to rehabilitate patients with late AMD. Magnetic and electrical fields improve impulse transmitting, activate intracellular and tissue regeneration of the retina. Recent findings are promising but require further in-depth studies. Keywords: age-related macular degeneration, retinal scar, gene therapy, stem cells, physiotherapy, rehabilitative medicine. For citation: Drakon A.K., Kurguzova A.G., Sheludchenko V.M., Korchazhkina N.B. Non-medical treatment for late age-related macular degeneration. Russian Journal of Clinical Ophthalmology. 2021;21(4):215–219 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-215-219.